Philosophical aspects of empathy as the main condition for the implementation of the principles of inclusive education - Kakimzhanova Margarita Kabdulayevna; Nukesheva Anar Zhaskairatovna; Mustafin Asset Kabdullayevich (Research Retrieval and Academic Letters, 2024)
Inclusiveeducation is notimportant in itself, andit is notonly the inclusion of childrenwithspecialneedsanddisabilitiesin the learningenvironment.This is,first of all, the creation of a newenvironment, taking into account a number of principlesin the organization of itslife. The mainone is thehumanization of the entiresystem of relations, the organization of interaction between the children’s andadultcommunitiesbasedonempathy. To showempathyis to accept the Otherasheis.Formedempathy,empathicpersonalitytendenciesare a fundamentalconditioninacceptingotherpeople, a manifestation of a flexiblepositiontowardsthem,andingeneral a humanizingprinciple of the entiresystem of relations.